THE EFFECT OF FORAGE AND CONCENTRATE IN DIETS TO RESPOND RUMEN FERMENTATION AND MICROBIAL PROTEIN SYNTHESIS OF BALI HEIFER CALVES - BUDIASA I K. M.; N. N. SURYANI; I W. SUARNA (Fakultas Peternakan Universitas Udayana, 2018)
In order to fulfill the domestic meat requirements and reduce imports so government continually develop localbeef cattle based on their quantity and quality of meat. Among the local cattle in Indonesia, Bali cattle is the mostfavourite cattle (32.31%) considering on its meat quality. There were 12 calves used in this research with 100 kgof average body weight. The treatments were diet with 40% concentrate and 60% king grass (A); 45% concentrateand 55% king grass (B); 50% concentrate and 50% king grass (C); 55% concentrate and 45% king grass (D). Theexperiment was design in a completely randomized block design with four treatments and three replicates. Thevariables measured were rumen fermentation as of pH, NH3, total and pastial of VFA (acetic acid, propionic acidand butyric acid), microbial protein synthesis and protozoa populations. It showed that treatment D produce thehighest NH3 and total VFA, 14.66 mMol, and 165.38 mMol respectively compared to other treatments. Propionicacid was 27.87 mMol the highest in treatment D and 368.62 g/h/d microbial protein synthesis. It can be concludedthe higher proportion of concentrate in the bali heifer calves so the more energy supply, in this case, SPM availabilityfor the host animal is higher.